Two lineages of kingfisher feather lice exhibit differing degrees of cospeciation with their hosts. Issue 8 (3rd May 2019) - Catanach, Therese A.; Johnson, Kevin P.; Marks, Ben D.; Moyle, Robert G.; Valim, Michel P.; Weckstein, Jason D.
Abstract: Unlike most bird species, individual kingfisher species (Aves: Alcedinidae) are typically parasitized by only a single genus of louse ( Alcedoffula, Alcedoecus, or Emersoniella ). These louse genera are typically specific to a particular kingfisher subfamily. Specifically, Alcedoecus and Emersoniella parasitize Halcyoninae, whereas Alcedoffula parasitizes Alcedininae and Cerylinae. Although Emersoniella is geographically restricted to the Indo-Pacific region, Alcedoecus and Alcedoffula are geographically widespread. We used DNA sequences from two genes, the mitochondrial COI and nuclear EF-1 α genes, to infer phylogenies for the two geographically widespread genera of kingfisher lice, Alcedoffula and Alcedoecus . These phylogenies included 47 kingfisher lice sampled from 11 of the 19 currently recognized genera of kingfishers. We compared louse phylogenies to host phylogenies to reconstruct their cophylogenetic history. Two distinct clades occur within Alcedoffula, one that infests Alcedininae and a second that infests Cerylinae. All species of Alcedoecus were found only on host species of the subfamily Halcyoninae. Cophylogenetic analysis indicated that Alcedoecus, as well as the clade of Alcedoffula occurring on Alcedininae, do not show evidence of cospeciation. In contrast, the clade of Alcedoffula occurring on Cerylinae showed strong evidence of cospeciation.